2022
DOI: 10.3389/fimmu.2022.1033770
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 booster vaccination rescues attenuated IgG1 memory B cell response in primary antibody deficiency patients

Abstract: BackgroundAlthough SARS-CoV-2 vaccines have proven effective in eliciting a protective immune response in healthy individuals, their ability to induce a durable immune response in immunocompromised individuals remains poorly understood. Primary antibody deficiency (PAD) syndromes are among the most common primary immunodeficiency disorders in adults and are characterized by hypogammaglobulinemia and impaired ability to mount robust antibody responses following infection or vaccination.MethodsHere, we present a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…However, other studies found little to no correlation between B-cell measurements and humoral response [97,129], likely due to patients receiving IgRT, where antibodies from product are indistinguishable from vaccine-induced antibodies. As with the T-cell response, Lin et al found a similar effect of a third vaccine dose increasing SARS-CoV-2-specific B-cell responses [87]. The previously mentioned individual with SASH3 deficiency had marked B-cell lymphopenia and reduced switched Bmem cells [129].…”
Section: Memory B Cells and Innate Cellsmentioning
confidence: 89%
See 3 more Smart Citations
“…However, other studies found little to no correlation between B-cell measurements and humoral response [97,129], likely due to patients receiving IgRT, where antibodies from product are indistinguishable from vaccine-induced antibodies. As with the T-cell response, Lin et al found a similar effect of a third vaccine dose increasing SARS-CoV-2-specific B-cell responses [87]. The previously mentioned individual with SASH3 deficiency had marked B-cell lymphopenia and reduced switched Bmem cells [129].…”
Section: Memory B Cells and Innate Cellsmentioning
confidence: 89%
“…Finally, to date assessments of vaccine responses in IEI patients have only been published up to 3-4 doses of COVID-19 vaccine [73,79,84,87,91,93,120]. While this has provided critical information on early post-vaccination immune responses, immune deficient individuals were recommended to receive boosters every 3-6 months.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The identi cation of switched memory B cells, characterized by increased absolute counts and CD19 expression, as protective factors (OR < 1) indicates their possible involvement in a bene cial immune response against endometritis. Switched memory B cells are known for their ability to rapidly produce speci c antibodies upon reexposure to antigens [15] , suggesting that a higher presence of these cells might enhance the body's capability to ght off infections associated with endometritis. Additionally, the protective association indicated by increased CD20 expression on IgD + CD38-unswitched memory B cells and a higher percentage of switched memory B cells among lymphocytes further supports the idea that an effective B cell-mediated immune response is crucial in safeguarding against endometritis.…”
Section: Discussionmentioning
confidence: 99%